Transformations of certain generalized Kampé de Fériet functions II. (1997) - Exton, Harold
Abstract : The development of identities of multivariable hypergeometric functions is further extended based upon the methods of the previous study (H. Exton, J. Phys. A29 (1996), 357-363) these functions occur in various applications in the fields of physics and quantum chemistry.